Employee Stock Option Valuation with Earnings-Based Vesting Condition - Patel, Kavir (African Institute of Financial Markets and Risk Management, 2019)
The valuation of employee stock options has become a key requirement due to the rapid growth in the use of these options as a means of employee compensation. IFRS 2 Share-based Payment stipulates that these instruments must be valued and expensed on the date the awards are issued. This dissertation aims to value an employee stock option, in a case where both the equity and vesting (performance) condition are based on a reported earnings process. The equity dependency on earnings stems from the fact that we are primarily concerned with the valuation of employee stock options that are issued by a private firm. We implement a capital structure framework provided by Goldstein, Ju and Leland (2001). In this framework, equity and debt are derived from an underlying EBIT process that is governed by a geometric Brownian motion. The model also accounts for taxation and bankruptcy. The research aim is addressed by incorporating the capital structure model into our employee stock option pricing framework.